Integrated Household Appliance Scheduling With Modeling of Occupant Satisfaction and Appliance Heat Gain - Zhao, Zehua; Luo, Fengji; Zhang, Yongxi; Ranzi, Gianluca; Su, Sheng (Frontiers in Energy Research, 2021)
With the prevalence of building automation and Internet-of-Things technologies, home energy management has become an active area in recent years. This paper proposes an integrated, multi-objective Home Energy Management System (HEMS), which optimally schedules controllable electric household appliances to balance three objectives: 1) home energy cost; 2) the occupant’s use satisfaction of controllable appliances; and 3) the occupant’s thermal comfort. In particular, the HEMS models the coupling operational relationship between the non-thermostatically controlled appliances and the air conditioner by investigating the impact of heat gains released by the appliances on the indoor temperature. An advanced multi-objective optimizer is applied to solve the home energy management model. Simulations are conducted to validate the proposed method.